Pelatihan Pembuatan Video Pembelajaran Berbasis Smartphone Android di KKG Kelas Gugus Pangeran Antasari Kota Banjarbaru - Muhammad Iqbal Ansari; Barsihanor Barsihanor; M. Fahmi Arifin (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The spread of covid-19 in Indonesia has a huge impact in the world of education. Responding to the outbreak of the Covid-19, the government has implemented a Distance Education for education sector. The impact of the problem is experienced by many classroom teachers in Banjarbaru City, among them 1). There are still many teachers who have minimal knowledge related to learning with distance education systems, 2), There are still low skills of teachers in the creation of IT-based learning media. To solve the problem there are several solutions that the advocates offer such as 1), Providing knowledge about managing learning with distance education systems. 2). Providing knowledge about the types media platforms for distance education. 3). Providing training on making learning videos based on android smartphones through kinemaster application. Based on the results of the training on making learning videos based on android smartphones through kinemaster applications in KKG teachers of Pangeran Antasari Group class of Banjarbaru City that is well carried out, it can be concluded that the training activities are able to provide new knowledge and skills for KKG teachers in Group class of Pangeran Antasari banjarbaru city in the creation of smartphone-based learning videos through kinemaster application.